Prevalence Distribution of Chronic Obstructive Pulmonary Disease (Copd) in the City of Osorno (Chile) in 2018 and Its Association with Fine Particulate Matter Pm2.5 Air Pollution - Maisey-Munoz, K (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Outdoor air pollution and biomass smoke exposure are related to the prevalence of chronic obstructive pulmonary disease (COPD). Since Osorno, Chile, is saturated with fine particulate matter (PM2.5), the aim of this work is to determine the prevalence distribution of COPD patients in the Primary Health Care (PHC) system in the city of Osorno, and its relationship with PM2.5. A cross-sectional descriptive study was carried out on COPD patients enrolled in the six PHC centers (PHCCs) of the city to assess the adjusted prevalence (population over 40 years). Gender- and territory-associated odds ratios (ORs) were also determined. In addition, an urban analysis of the distribution of PM2.5 and an exploratory analysis of the spatial behavior of enrolled COPD patients through featured binning were carried out. In 2018, the city of Osorno had 809 enrolled COPD patients in the PHC system (55.1% female), with a 1.3% age-adjusted prevalence (inhabitants over 40 years old), which was 11.7% after underdiagnosis correction. The COPD patients were mainly between 70 and 79 years old (34.3%). The urban area under the administration of the PHCC Rahue Alto (PHCC-RA) had a higher OR (1.98 [1.73–2.26]) compared to the situation of the city. Also, air pollution (PM2.5) was the highest in the PHCC-RA area, which could account for the observed prevalence. The number of COPD patients in this area is the highest in the commune, which increases the risk of complications derived from the disease and air pollution. Thus, territories with the highest COPD prevalence have the largest OR, which could complicate patients’ condition due to the high levels of outdoor air pollution. © 2024 by the authors.